Model of chemical conversion initiation in the adhesive bonding layer during roll motion in the process of laminated object creation; Nanoscience and Technology: An International Journal; Vol. 9, iss. 1 - Knyazeva A. G. Anna Georgievna (2018, 2018)
Title screen